PENDAMPINGAN LEGALITAS SEBAGAI STRATEGI PENINGKATAN DAYA SAING UMKM: BUKTI EMPIRIS DARI PROGRAM NIB DAN SERTIFIKASI HALAL - Katri Gentari; Heriyana Heriyana; Neti Erlina; Sri Agustina; Emelda Emelda (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The low level of business legality ownership remains a major challenge faced by many Micro, Small, and Medium Enterprises (MSMEs), particularly regarding the Business Identification Number (NIB) and halal certification. Limited regulatory literacy and administrative capacity often prevent business actors from independently managing the legalization process. This study aims to analyze the effectiveness of a business legality assistance program in improving the literacy, readiness, and formalization of MSMEs. This research employed a quantitative approach using a one-group pretest–posttest design involving 25 MSME participants who took part in an assistance program for obtaining NIB and halal certification. Data were collected through Likert-scale questionnaires measuring regulatory understanding, administrative readiness, and perceptions of business legality. Data analysis was conducted using descriptive statistics and a paired sample t-test to examine differences before and after the intervention. The results show a significant improvement across all measured indicators. The average scores of understanding and readiness increased from 1.96–2.20 in the pretest to 4.68–4.84 in the posttest, with a significance value of p < 0.05. In addition, 23 MSMEs successfully obtained NIB, while all participants submitted applications for halal certification. These findings indicate that practical and participatory assistance effectively enhances literacy and readiness while accelerating MSME formalization. Structured assistance programs therefore have the potential to serve as an effective empowerment model to improve legal compliance and strengthen business competitiveness. ABSTRAK Rendahnya tingkat kepemilikan legalitas usaha masih menjadi kendala yang dihadapi oleh banyak pelaku Usaha Mikro, Kecil, dan Menengah (UMKM), khususnya terkait Nomor Induk Berusaha (NIB) dan sertifikasi halal. Keterbatasan literasi regulasi dan kemampuan administratif menyebabkan pelaku usaha belum sepenuhnya mampu mengurus legalitas secara mandiri. Penelitian ini bertujuan untuk menganalisis efektivitas program pendampingan legalitas usaha dalam meningkatkan literasi, kesiapan, dan realisasi formalitas UMKM. Penelitian menggunakan pendekatan kuantitatif dengan desain one group pretest–posttest terhadap 25 pelaku UMKM yang mengikuti program pendampingan pengurusan NIB dan sertifikasi halal. Data dikumpulkan melalui kuesioner skala Likert yang mengukur pemahaman regulasi, kesiapan administratif, dan persepsi terhadap legalitas usaha. Analisis data dilakukan menggunakan statistik deskriptif dan uji paired sample t-test untuk melihat perbedaan sebelum dan sesudah intervensi. Hasil penelitian menunjukkan adanya peningkatan signifikan pada seluruh indikator yang diukur. Nilai rata-rata pemahaman dan kesiapan meningkat dari kisaran 1,96–2,20 pada pretest menjadi 4,68–4,84 pada posttest dengan nilai signifikansi p < 0,05. Selain itu, 23 UMKM berhasil memperoleh NIB dan seluruh peserta telah mengajukan sertifikasi halal. Temuan ini menunjukkan bahwa pendampingan yang bersifat praktis dan partisipatif efektif meningkatkan literasi, kesiapan, serta mendorong percepatan formalisasi UMKM. Program pendampingan terstruktur berpotensi menjadi model pemberdayaan untuk meningkatkan kepatuhan legalitas dan daya saing usaha.